Optimization of Physical Fitness Development for Primary School Learners in Physical Education Lessons (Baltic Journal of Sport and Health Sciences, 2014)
Background. Nowadays, an urgent social problem in sovereign Kazakhstan, which defines the strategy of social development of our society, is upbringing a new person developed spiritually, morally and physically. Physical fitness  of  primary  school  learners  as  a  sphere  of  scientific-pedagogical  knowledge  in  Kazakhstan  Republic  has not been fully researched. It conditioned the problem of our investigation – to substantiate theoretically and work out the methodology of optimization of physical fitness development for primary school learners in PE lessons. Theoretical analysis of scientific works suggests that physical fitness of primary school learners as a sphere of scientific-pedagogical knowledge has not been fully investigated. Despite the diversity of issues and theoretical as well as practical pedagogical research, it should be noted that the problem of physical fitness of primary school learners using sport games in PE lessons is still open for theoretical consideration and experimental research.Research aim was to define the most effective methodology of physical fitness of 8–9 year- old boys in PE lessons using elements of football in general education schools. Methods. All in all there were 102 boys. They were divided into 4 groups – 3 experimental groups and 1 control group. During the experiment, 75% of time for teaching technical actions of football was devoted for group E1 ,  for E2 – 50%, and for E3 – 25%; for physical fitness –25, 50 and 75% respectively. During the experiment, with the help of methods given above, we covered the following aspects: physical development, general physical fitness, special fitness.Results. Analyzing the increase in overall physical fitness for the whole period of the experiment, we observed a significant increase in all of the surveyed groups (p  < .05–.001). All the tested groups were approximately of the same level. Conclusions. The study showed that the best option for physical training for primary school children in physical education classes in comprehensive schools was to have 75% of the total lesson time to the development of physical fitness and 25% of the lesson time  – to technical training (program C). Physical education classes with elements of football contribute to more intense dynamics of indicators of general and special training of 8–9-year-old boys. Analysis of the studied parameters of fitness and technique of playing football has shown that methods of education and physical qualities of technical preparation, which was given to the third experimental group, contributed to the development of better skills in football.Keywords: physical education lessons, physical, technical fitness, football.